Aspekty finansowe międzynarodowego cyklu życia produktu - Grzegorczyk, Wojciech (Financial Aspects of International Life Cycle of Product, 2006)
Financial decisions of a firm during a product life cycle on the international market are specially important. They refer to a choice of financial sources for creating of the new product and management of current assets during the life cycle of the product on the international market. In the first stage of life cycle of product on the international market an enterprise exports the new product to developed countries and then places its production there. In the second stage, willing to reduce its costs, the enterprise exports the product to poorly developed countries. Sometimes the production is also moved to these countries. In the last stage the enterprise sells the product's licence. The firm also imports the product because in its country there is still a demand for it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 257-264